Factor affecting the young people to use public open space. case study: Dataran Centrio Seremban 2, Negeri Sembilan - Md Ariffin, Mohamad Azrin; Hussain, Norhuzailin; Hussein, Mohd Kher (Institut Penyelidikan Pembangunan Belia Malaysia, Kementerian Belia dan Sukan Malaysia, 2018)
Public open space is a main component of urban space that caters the urban public life daily. In Malaysia, the number of open spaces that are gazetted by the local authority is increasing in line with the rapid development of new areas. Indeed, public open spaces, such as parks and green spaces appear to be key built environment settings that provide opportunities for a variety of physical activity. However, not all public open spaces are equally effective in promoting physical activities. The existing public open space is still lacking of appropriate space for young people to do physical activities. This area is given less emphasis on young people because it was designed for various type of people. Young people as they are energetic and eager to explore new experience, they need some space to spend their leisure time and to express themselves with the activities. This study attempts to answer these questions by carrying out survey using questionnaire to explore factors that affect the use of public open space as place for physical activities and to recommend measures for improving the use of public open space for physical activities. In order to answer these objectives, survey was conducted among a random sample of young people (n=100) who visited Dataran Centrio, Seremban 2. Data collected was analysed using SPSS 19 and the result showed the activities the young people that are engaged in and factors that influenced them to use the space for physical activities. The study found that most of the respondents preferred to do physical activities because of the facilities provided.